Diversity of Catechin in Northeast Indian Tea Cultivars - Santanu Sabhapondit; Tanmoy Karak; Lakshi Prasad Bhuyan; Bhabesh Chandra Goswami; Mridul Hazarika (The Scientific World Journal)
Tea (Camellia sinensis L.) leaf contains a large amount of catechins (a group of very active flavonoids) which contribute to major quality attributes of black tea. Based on morphological characters tea plants were classified as Assam, China, and Cambod varieties. The present study is an attempt for biochemical fingerprinting of the tea varieties based on catechin composition in green leaf of cultivars grown in Northeast India. Assam variety cultivars contained the highest level of catechins followed by Cambod and China. The average catechin contents were 231 ± 7 mg g-1, 202 ± 5 mg g-1, and 157 ± 4 mg g-1 of dry weight of green leaf for Assam, Cambod, and China cultivars, respectively. Among the individual catechins the variations in epigallocatechin gallate (EGCG) and epigallocatechin (EGC) were the most prominent among the varieties. High EGC content was found to be a characteristic of Assam variety which was further corroborated through multivariate analysis.